A longitudinal study of the association between attending cultural events and coronary heart disease - Sven-Erik Johansson; Filip Jansåker; Kristina Sundquist; Lars Olov Bygren (Communications Medicine, 2023)
Abstract Background The experiences of art and music are an essential part of human life and this study aimed to examine the longitudinal association between cultural participation and coronary heart disease. Methods This was a longitudinal study on a randomly selected representative adult cohort (n = 3296) of the Swedish population. The study period was over 36 years (1982–2017) with three separate eight-year interval measurements of cultural exposure (for example, visiting theatres and museums) starting in 1982/83. The outcome was coronary heart disease during the study period. Marginal structural Cox models with inverse probability weighting were used to account for time-varying weights of the exposure and potential confounders during the follow-up. The associations were also examined through a time-varying Cox proportional hazard regression model. Results Cultural participation shows a graded association, the higher the exposure the lower the risk of coronary heart disease; the hazard ratio was 0.66 (95% confidence interval, 0.50 to 0.86) for coronary heart disease in participants with the highest level of cultural exposure compared with the lowest level. Conclusion Although causality cannot be determined due to the remaining risk of residual confounding and bias, the use of marginal structural Cox models with inverse probability weighting strengthens the evidence for a potentially causal association with cardiovascular health, which warrants further studies.